Influence Of Sowing Date And Norms On The Place Of The Lower First Pod Of Lentil Varieties (Texas Journal of Multidisciplinary Studies, 2021)
This article provides data on the norms and date of sowing, the location of the first pod of lentil varieties. In lentil varieties, the location of the lower first pod was found to be 1.9-3.2 cm higher in the Oltin don variety and 3.0-3.5 cm higher in the Darmon variety when the planting norms were exceeded. When lentil varieties were planted in the autumn and spring, the location of the lower first pod was found to be 0.1–0.2 cm, or homogeneous, and it was found that lentil varieties could be harvested without destroying the crop grown when the sowing norm increased.